Identification of Novel Inhibitors of Auxin-Induced Ca2+ Signaling via a Plant-Based Chemical Screen. Issue 1 (8th February 2019) - De Vriese, Kjell; Himschoot, Ellie; Dünser, Kai; Nguyen, Long; Drozdzecki, Andrzej; Costa, Alex; Nowack, Moritz K.; Kleine-Vehn, Jürgen; Audenaert, Dominique; Beeckman, Tom; Vanneste, Steffen
Abstract : Screening of an annotated library of biologically active molecules for inhibitory effects on auxin-induced Ca 2+ entry in BY-2 cells yielded several new inhibitors for investigating Ca 2+ signaling. Abstract: Many signal perception mechanisms are connected to Ca 2+ -based second messenger signaling to modulate specific cellular responses. The well-characterized plant hormone auxin elicits a very rapid Ca 2+ signal. However, the cellular targets of auxin-induced Ca 2+ are largely unknown. Here, we screened a biologically annotated chemical library for inhibitors of auxin-induced Ca 2+ entry in plant cell suspensions to better understand the molecular mechanism of auxin-induced Ca 2+ and to explore the physiological relevance of Ca 2+ in auxin signal transduction. Using this approach, we defined a set of diverse, small molecules that interfere with auxin-induced Ca 2+ entry. Based on annotated biological activities of the hit molecules, we found that auxin-induced Ca 2+ signaling is, among others, highly sensitive to disruption of membrane proton gradients and the mammalian Ca 2+ channel inhibitor bepridil. Whereas protonophores nonselectively inhibited auxin-induced and osmotic stress–induced Ca 2+ signals, bepridil specifically inhibited auxin-induced Ca 2+ . We found evidence that bepridil severely alters vacuolar morphology and antagonized auxin-induced vacuolar remodeling. Further exploration of this plant-tailored collection of inhibitors will lead to a better understanding of auxin-induced Ca 2+ entry and its relevance for auxin responses.